2012
DOI: 10.4103/0971-9784.95072
|View full text |Cite
|
Sign up to set email alerts
|

A randomized prospective analysis of alteration of hemostatic function in patients receiving tranexamic acid and hydroxyethyl starch (130/0.4) undergoing off pump coronary artery bypass surgery

Abstract: Postoperative hemorrhagic complications is still one of the major problems in cardiac surgeries. It may be caused by surgical issues, coagulopathy caused by the side effects of the intravenous fluids administered to produce plasma volume expansion such as hydroxyl ethyl starch (HES). In order to thwart this hemorrhagic issue, few agents are available. Fibrinolytic inhibitors like tranexamic acid (TA) may be effective modes to promote blood conservation; but the possible complications of thrombosis of coronary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 17 publications
(25 reference statements)
2
15
0
Order By: Relevance
“…45 Two trials have examined the impact of TXA on TEG markers of fibrinolysis in cardiac surgery, yielding conflicting conclusions. 46,47 To our knowledge, none of the trials identified measured the impact of TXA on PAP complex levels.…”
Section: Discussionmentioning
confidence: 99%
“…45 Two trials have examined the impact of TXA on TEG markers of fibrinolysis in cardiac surgery, yielding conflicting conclusions. 46,47 To our knowledge, none of the trials identified measured the impact of TXA on PAP complex levels.…”
Section: Discussionmentioning
confidence: 99%
“…experimental group (two doses of TXA) and a control group (normal saline), but the results were not statistically significant. Chakravarthy et al (28) used TEG to compare the influence of TXA and hydroxyethyl starch on extracorporeal circulation blood loss during heart surgeries; however, these results were not statistically significant either. Due to limited funding, TEG could not be used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The characteristics of included studies were shown in [12,14,[16][17][18][23][24][25][26]28,[30][31][32]34,36,38,39], off-pump condition in 9 trails [3,10,11,15,27,29,33,35,37] and both condition in 2 trails [4,8].…”
Section: Description Of Included Studiesmentioning
confidence: 99%
“…14 studies [3,11,12,14,16,[23][24][25][27][28][29][30]35,38] did not provide a satisfactory description of their random processes. Blinding process was at high risk of bias in one study [39] and unclear risk of bias in 7 studies [11,12,[23][24][25]29,35] due to unclear description. 3 studies [16,25,31] had unclear or incomplete descriptions of their outcome data.…”
Section: Risk Of Bias Within Studiesmentioning
confidence: 99%
See 1 more Smart Citation